Therapeutic effect of antimyeloma antibodies conjugated with gold nanoparticles on the growth of myeloma cell line - Abdalla, M S; Sharada, H M; Mostafa, K A; Azzam, E S; Ali, E N; Abdel-Ghany, I Y; Ayad, E.G.A (International Multidisciplinary Research Journal, 2012)
Nanobiotechnology is a field of biomedical application of nanosize system which is a rapidly developing area within nanotechnology among these nonmaterial, gold nanoparticles (AuNPs) which receive a significant attention due to their unique physical, chemical and biological properties. AuNPs and bio-conjugated AuNPs have been widely used in cancer treatment besides other application on cancer detection and diagnosis. In this study the potential therapeutic effects of polyclonal Antimyeloma antibody (AbMM) conjugated to AuNPs in comparison with naked (AbMM) or AuNPs alone in modulation of proliferation capacity in vitro and different stages of MM cell cycle have been evaluated besides evaluation of their effects on tumor growth delay. Effect of AuNPs , (AbMM) and (Nanogold -Antimyeloma Antibodies conjugate) (gold-AbMM) on growth of myeloma cells showed decreasing in multiple myeloma SP2OR (MM) viability with increasing dose of these treatments compared to that of control also a significant enhancement in the apoptosis after conjugation of Nanogold to the Antimyeloma was observed. The induction of apoptosis with gold-AbMM was significantly higher than the MM cells exposed to only AbMM or AuNPs. The study concluded that the efficacy of (gold-AbMM) on induced myeloma growth inhibition is better than that of individual AuNPs and AbMM.